Deactivatable Bisubstrate Inhibitors of Protein Kinases - Tanel Sõrmus; Darja Lavogina; Erki Enkvist; Asko Uri; Kaido Viht (Molecules, 2022)
Bivalent ligands, including bisubstrate inhibitors, are conjugates of pharmacophores, which simultaneously target two binding sites of the biomolecule. Such structures offer attainable means for the development of compounds whose ability to bind to the biological target could be modulated by an external trigger. In the present work, two deactivatable bisubstrate inhibitors of basophilic protein kinases (PKs) were constructed by conjugating the pharmacophores via linkers that could be cleaved in response to external stimuli. The inhibitor ARC-2121 incorporated a photocleavable nitrodibenzofuran-comprising β-amino acid residue in the structure of the linker. The pharmacophores of the other deactivatable inhibitor ARC-2194 were conjugated via reduction-cleavable disulfide bond. The disassembly of the inhibitors was monitored by HPLC-MS. The affinity and inhibitory potency of the inhibitors toward cAMP-dependent PK (PKAcα) were established by an equilibrium competitive displacement assay and enzyme activity assay, respectively. The deactivatable inhibitors possessed remarkably high 1–2-picomolar affinity toward PKAcα. Irradiation of ARC-2121 with 365 nm UV radiation led to reaction products possessing a 30-fold reduced affinity. The chemical reduction of ARC-2194 resulted in the decrease of affinity of over four orders of magnitude. The deactivatable inhibitors of PKs are valuable tools for the temporal inhibition or capture of these pharmacologically important enzymes.